IMPLEMENTASI KURIKULUM K-13 YANG DISESUAIKAN DENGAN KURIKULUM MERDEKA DI SLB-A PRPCN PALEMBANG - Astuti, Mardiah; Marlina, Leny; Saprullah, Saprullah; Irvan, Indra Ari; Fitrianti, Eka (STKIP Pesisir Selatan, 2024)
Education for children with special needs is education that is adapted to the child's physical, intellectual, emotional and social needs. This research evaluates the implementation of the K-13 Curriculum Adapted to the Independent Curriculum for Children with Special Needs at SLB-A PRPCN Palembang, using a qualitative case study method. Research results show good progress, but there are still obstacles such as a lack of qualified teachers and adequate learning facilities. To improve the quality of education for children with special needs, continuous efforts are needed in organization, motivation and coordination. Supporting factors include appropriate teacher qualifications and collaboration with other schools, while inhibiting factors include inadequate teacher qualifications and a lack of learning media. In its conclusion, this research emphasizes the importance of continued efforts in overcoming challenges in implementing the curriculum for the education of children with special needs. This can be achieved by improving teacher qualifications, learning facilities, and considering supporting and inhibiting factors. It is hoped that this effort can improve the quality of education for children with special needs at SLB-A PRPCN Palembang.